Dynamic Pattern of HOXB9 Protein Localization during Oocyte Maturation and Early Embryonic Development in Mammals - Sauvegarde, Caroline (PLoS One, 2016)
BACKGROUND: We previously showed that the homeodomain transcription factor HOXB9 is expressed in mammalian oocytes and early embryos. However, a systematic and exhaustive study of the localization of the HOXB9 protein, and HOX proteins in general, during mammalian early embryonic development has so far never been performed. RESULTS: The distribution of HOXB9 proteins in oocytes and the early embryo was characterized by immunofluorescence from the immature oocyte stage to the peri-gastrulation period in both the mouse and the bovine. HOXB9 was detected at all studied stages with a dynamic expression pattern. Its distribution was well conserved between the two species until the blastocyst stage and was mainly nuclear. From that stage on, trophoblastic cells always showed a strong nuclear staining, while the inner cell mass and the derived cell lines showed important dynamic variations both in staining intensity and in intra-cellular localization. Indeed, HOXB9 appeared to be progressively downregulated in epiblast cells and only reappeared after gastrulation had well progressed. The protein was also detected in the primitive endoderm and its derivatives with a distinctive presence in apical vacuoles of mouse visceral endoderm cells. CONCLUSIONS: Together, these results could suggest the existence of unsuspected functions for HOXB9 during early embryonic development in mammals.